Pelayanan Kepada Lembaga Pemasyarakatan (LP) Sebagai Upaya Meminimalisasi Kejahatan - Rencan Carisma Marbun (Jurnal Teologi Cultivation, 2020)
Abstract.This research raises the title "Services to Correctional Institutions (LP) as an effort to minimize crime". The purpose of this study is to describe how services to correctional institutions are an effort to minimize crime.The service meant is an activity that occurs in direct interaction between one person and another. In other words, service is described as an effort to serve the needs of others that lead to change. In this case the service can be carried out by the family / family, the church, the government and the existence of community acceptance to the correctional institutions in an effort to minimize crime and the practical goal is to bring them into change (repentance).Key words: service, correctional institutions, effort, crime